2016
DOI: 10.1007/s10570-016-1121-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TEMPO-oxidised cellulose nanofibrils on the properties of filler-containing papers

Abstract: 18In this work, cellulose nanofibrils (CNF) were produced from a Eucalyptus globulus bleached

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…Recent studies have investigated the effects of pulp source (Tanaka et al 2016), fibril dimension and concentration (Agoda-Tandjawa et al 2010), mechanical treatments (Pääkkö et al 2007), ionic strength (Dong et al 2013), pH (Fall et al 2013), as well as addition of amphiphilic molecules (Quennouz et al 2016) on the rheology of CNF dispersions. Additionally, CNFs can also assist in preparation of homogeneous dispersions of a variety of fillers and pigments, such as carbon nanotubes (Hamedi et al 2014), reduced graphene oxide (Duan et al 2016), TiO 2 (Schütz et al 2012), and CaCO 3 (Lourenço et al 2016) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the effects of pulp source (Tanaka et al 2016), fibril dimension and concentration (Agoda-Tandjawa et al 2010), mechanical treatments (Pääkkö et al 2007), ionic strength (Dong et al 2013), pH (Fall et al 2013), as well as addition of amphiphilic molecules (Quennouz et al 2016) on the rheology of CNF dispersions. Additionally, CNFs can also assist in preparation of homogeneous dispersions of a variety of fillers and pigments, such as carbon nanotubes (Hamedi et al 2014), reduced graphene oxide (Duan et al 2016), TiO 2 (Schütz et al 2012), and CaCO 3 (Lourenço et al 2016) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The microparticle is usually anionic bentonite or microsilica. Recently, several authors have observed that the use of CNF as a microparticle, in combination with a polyelectrolyte, such as polyacrylamide (PAM), improves the retention of fillers and the mechanical properties without a detrimental effect on drainage (Table 1) [35,41,57]. Petroudy et al [58] showed that it is possible to achieve a high tensile index (TI) increment by combining CNF and cationic PAM (CPAM) without increasing the drainage time.…”
Section: Wet-end Optimizationmentioning
confidence: 99%
“…Moreover, with the use of chitosan and 1 wt% CNF, the drainage rate was increased by 50% and the paper sheets achieved a TI improvement of 16% and 14% when CNF are from bleached Eucalyptus Kraft pulp and corn stalk organosolv pulp, respectively. Lourenço et al [57] found that the oxidation degree of CNF was closed related to their effect on filler retention. The excess of oxidation led to a CNF with too high carboxylic content and too low polymerization degree with low filler flocculation ability and with high affinity to CPAM, forming CPAM-CNF bundles that were not able to attach the filler to the fibers.…”
Section: Wet-end Optimizationmentioning
confidence: 99%
“…Diatomite (DM) is a low‐cost, environmentally friendly, and natural microstructured/nanostructured material derived from sedimentary silica. It has cylindrical and plate morphologies with well‐developed mesoporous and/or macroporous structures . The highly developed pore structure, low density, and high surface area of DM results in it having a number of industrial applications, including as filtration media for various inorganic and organic chemicals and absorbents …”
Section: Introductionmentioning
confidence: 99%
“…They may have a negative impact on the effectiveness of cationic additives and may be unable to firmly anchor anionic trash onto pulp fibers. Nowadays, there have been plenty of studies on the application of ATCs in anionic trash elimination . However, the use of ATCs to modify the DM surface and the application of the modified product to the papermaking process have not been reported.…”
Section: Introductionmentioning
confidence: 99%